Pulse pressure waveform analysis compared to doppler ultrasonography as a screening tool for hypertensive pregnancy. (18th April 2012) - Hogan, JL; Kennelly, MM; O'Dwyer, V; O'Reilly, A; Turner, MJ; Stuart, B
Abstract : Pre-eclampsia is a hypertensive disorder unique to pregnancy. Accurate prediction of the development of pre-eclampsia is still elusive. Uterine artery Doppler provides information regarding blood flow within the vascular system. Information on the elasticity in the vessel wall is obtained from pulse pressure analysis. The purpose of this prospective study was to compare uterine artery Doppler indices with pulse pressure waveform analysis in the prediction of pre-eclampsia in low-risk pregnancy. Patients were recruited from the antenatal clinic. Each patient had uterine artery Doppler and pulse pressure waveform analysis performed in the second trimester. Data on pregnancy outcomes were obtained and the main outcome measure was the development of pre-eclampsia. Logistic regression was used to evaluate the parameters as predictors of pre-eclampsia. Forty one patients were recruited into the study. Pre-eclampsia occurred in 2 (4.9%) of the pregnancies which equates to a prior risk of 1 in 21. Small artery elasticity (p=0.02) and systemic vascular resistance (p=0.005) were shown to differ in patients with pre-eclampsia as did the mean arterial pressure (p=0.01). There was no difference seen in uterine artery Doppler pulsatility index in the pre-eclamptic pregnancies compared to normal pregnancy. Pulse pressure waveform analysis shows promise as a screening tool for pre-eclampsia. This study is the first to compare elasticity, using the diastolic phase of the cardiac cycle, and uterine artery Doppler ultrasound in pregnancy as a predictor of pre-eclampsia. A larger study should be undertaken to further evaluate pulse pressure waveform analysis.